2022
DOI: 10.1001/jama.2022.10461
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 4% Albumin Solution vs Ringer Acetate on Major Adverse Events in Patients Undergoing Cardiac Surgery With Cardiopulmonary Bypass

Abstract: In cardiac surgery, albumin solution may maintain hemodynamics better than crystalloids and reduce the decrease in platelet count and excessive fluid balance, but randomized trials are needed to compare the effectiveness of these approaches in reducing surgical complications.OBJECTIVE To assess whether 4% albumin solution compared with Ringer acetate as cardiopulmonary bypass prime and perioperative intravenous volume replacement solution reduces the incidence of major perioperative and postoperative complicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 16 publications
0
36
1
2
Order By: Relevance
“…Even if no difference was found concerning the incidence of clinically important adverse cardiac events, albumin significantly reduced the postoperative plasma creatine kinase-MB. This finding could be explained by the protective role of albumin on the coronary glycocalyx [ 19 ]. Even if, to our knowledge, no study using HA has been used on mechanical circulatory support during lung transplantation, it is important to highlight that human albumin is one of the main components of Steen’s solution used in the ex vivo lung perfusion with the Toronto protocol [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even if no difference was found concerning the incidence of clinically important adverse cardiac events, albumin significantly reduced the postoperative plasma creatine kinase-MB. This finding could be explained by the protective role of albumin on the coronary glycocalyx [ 19 ]. Even if, to our knowledge, no study using HA has been used on mechanical circulatory support during lung transplantation, it is important to highlight that human albumin is one of the main components of Steen’s solution used in the ex vivo lung perfusion with the Toronto protocol [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…for a permanent pacemaker) with use of albumin compared to ringer acetate after cardiac surgery. 24 While perinexal conduction was altered with in-vitro studies of albumin versus mannitol solutions, human metabolism, and interstitial fluid exhibit much greater regulation. Infused albumin typically has a half-life of around 110 min in healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective studies have since shown improved mortality and less positive fluid balance with albumin use compared to crystalloids in cardiac surgery 22,23 . A single‐center prospective clinical trial (NCT02560519) was recently published by Pesonen et al, and found no significant difference in adverse events, including arrhythmias (defined as ventricular arrhythmias, POAF, or need for a permanent pacemaker) with use of albumin compared to ringer acetate after cardiac surgery 24 …”
Section: Discussionmentioning
confidence: 99%
“…In terms of the choice of crystalloid, perioperative use of chloride liberal intravenous fluid was found to be associated with hyperchloremic metabolic acidosis and increased postoperative AKI in patients who underwent off-pump coronary artery bypass grafting surgery [ 130 ]. When compared with Ringer acetate, 4% albumin solution for priming CPB and perioperative venous volume replacement solution cannot reduce the incidence of CSA-AKI [ 131 ].…”
Section: Strategies For Csa-aki Preventionmentioning
confidence: 99%